Synthesis and Characterization of Acid Doped Polyaniline for Super Capacitor Application - Bhattarai, Santosh; Devkota, Nim Bahadur; Neupane, Shova; Gupta, Deepak Kumar; Yadav, Amar Prasad (Journal of Nepal Chemical Society, 2017)
Available with fulltext